Paper recycling framework, the "Wheel of Fiber". (1st June 2016) - Ervasti, Ilpo; Miranda, Ruben; Kauranen, Ilkka
Abstract: At present, there is no reliable method in use that unequivocally describes paper industry material flows and makes it possible to compare geographical regions with each other. A functioning paper industry Material Flow Account (MFA) that uses uniform terminology and standard definitions for terms and structures is necessary. Many of the presently used general level MFAs, which are called frameworks in this article, stress the importance of input and output flows but do not provide a uniform picture of material recycling. Paper industry is an example of a field in which recycling plays a key role. Additionally, terms related to paper industry recycling, such as collection rate, recycling rate, and utilization rate, are not defined uniformly across regions and time. Thus, reliably comparing material recycling activity between geographical regions or calculating any regional summaries is difficult or even impossible. The objective of this study is to give a partial solution to the problem of not having a reliable method in use that unequivocally describes paper industry material flows. This is done by introducing a new material flow framework for paper industry in which the flow and stage structure supports the use of uniform definitions for terms related to paper recycling. This new framework is termed the Detailed Wheel of Fiber. Graphical abstract: Highlights: There is no reliable method in use to unequivocally describe paper material flows. A new material flow framework, called the Detailed Wheel of Fiber, was introduced. Uniform terminology and standard definitions for terms and structures was developed. A new formula for calculating the paper recycling rate was proposed.